Evaluation of the Excellent Class Program in Improving the Quality of Education in Junior High Schools. Muhammadiyah - Bandung - Yulianti Fiyul, Arfiani (The International Journal of Education Management and Sociology, 2024)
This study applies the Context, Input, Process, Product (CIPP) program evaluation model with a descriptive qualitative approach. Data collection refers to the CIPP evaluation instrument table which is compiled based on predetermined criteria, through observation, interview, and documentation techniques. Data analysis involves data collection, data reduction, data presentation, drawing conclusions, and data verification. The results show 1. Evaluation of the program context in the number of students who have talents and creativity that are facilitated more optimally. The excellent class program to create superior students and shows that Muhammadiyah schools have quality students. 2. The Input Evaluation applied includes student screening, testing, willingness to join the excellent class. 3. Evaluation of the program performance process is not optimal. The relationship between the implementer and students is going well, with full trust from the parents of students regarding student development. 4. Evaluation of the program's product results showed good achievements, although not yet fully maximized. 80% of Muhammadiyah graduates successfully continued their education to favorite state schools. The superior class program to be continued with the condition of reformulating the initial objectives of the program.